The Relationship between Confidence Level and the Decision to Take Remote Shooting in Futsal Players of the Excellent Sport Club Bogor City Team - Faqih Hidayat; Yudha Munajat Saputra; Syam Hardwis (Universitas Negeri Semarang, 2026)
This study aims to analyze the relationship between self confidence and long-range shooting decision-making in futsal players of the Bogor City Excellent Sport Club Team. The study used a quantitative approach with a correlational design to test the relationship between psychological variables and players' tactical behavior in the context of futsal matches. The research subjects consisted of 30 futsal players who were selected using saturated sampling techniques, so that the entire population was used as a research sample. The level of self-confidence was measured using the State Sport Confidence Inventory (SSCI), while shooting decision-making was measured using the Scale Of Effective Decision-Making Sport (SEDMS) which was equipped with observation of player performance on the field. Data analysis was carried out using SPSS software, including descriptive static, Shapiro-Wilk normality test, and Spearman correlation test as inferential analysis. The results of the analysis showed that the selft confidence level of futsal players was in the relatively high category, while the shooting decision-making ability was in the medium category. The normality test showed that the SSCI data was normally distributed, while the SEDMS data was not normally distributed, so the relationship analysis was carried out using the Spearman correlation test. The results of the correlation test showed a very weak and insignificant positive relationship between self confidence and shooting decision-making (r = 0.091; p > 0.05). These findings indicate that self-confidence has no meaningful relationship with long-range shooting decision-making. Thus, shooting decision-making in futsal games is influenced by various other factors outside of confidence, such as technical readiness, tactical understanding, match experience, and match situational conditions.